69 Continuous and Regular Live Feedback is Required to Maintain An Improvement in the Quality of Discharge Summaries. Shop 75 +. (16th March 2021) - Cross, H; Evans, J; Pederson, A; Yidana, D; Carey, D; Robey, R; Vilches-Moraga, A; Gaillemin, O
Abstract: Background: This quality improvement project aims to improve communication between secondary and primary care at the time of hospital discharge of older patients. Introduction: Discharge summaries (DS) are a key component of communication between secondary and primary care. Poor quality DS are associated with poorer outcomes in terms of adverse events [1], readmissions [2] and medication errors [3]. There is NICE and AMRC guidance on what constitutes a good DS [4, 5]. Method: Prospective review of DS from a range of wards was completed in August 2017 against a detailed data tool. A random selection of DS from the same wards was audited monthly from November 2017 onwards. A novel live-feedback system was introduced to the same wards in February 2018 so that the teams completing DS received feedback on how well their summaries complied with the recommendations and what areas needed improvement. A change in staffing lead to a break in the delivery of monthly feedback to the ward teams from April to September 2019 when it was re-commenced. Results: In the majority of areas there has been an increase in the quality of the DS from the beginning of the project until March 2019 when the regular feedback interventions were suspended. There was a decrease in the quality of summaries in July and August 2019, followed by an increase as regular feedback interventions recommenced in September 2019. The aggregate results of the four main components of DS (follow-up actions, medicines, clinical summary, and functional assessment), scored "good" in 13% of DS at baseline, 40% in March 2019, 20% in July 2019 and 31% in October 2019. Conclusions: The suspension of regular direct interventions resulted in a significant deterioration in the quality of discharge summaries, and this improved quickly after reintroduction of PDSA cycles in key areas. Continuous quality improvement requires uninterrupted focus on regular live feedback. References: 1. Clegg et al. Lancet 2013; 381: 752–62. 2. Samra et al. Age Ageing 2017; 46: 911–9. 3. Romero-Ortuno et al. Age Ageing 2012; 41: 684–9.